Built-Environment Interventions and Urban Sustainability: Evidence on Energy Use, Travel Behaviour, and Traffic Safety - Ravazdezh, Fatemeh (Université d'Ottawa / University of Ottawa, 2026)
Urban areas are complex socio-economic and ecological systems in which political, economic, social, natural, and built components are tightly interlinked. As growing hubs of population and activity, cities concentrate energy use and greenhouse gas emissions, particularly in the building and transport sectors, while also facing local sustainability challenges such as heat exposure, congestion, and traffic risk. Improving urban sustainability and decarbonizing cities therefore depends critically on managing energy demand and consumption patterns in transport and building sector. Physical components of urban areas including land use patterns, buildings and open spaces, and road and transportation network play an integral role in urban carbon emissions as they form the long-lasting skeletons of the city with the ability to lock in energy consumption patterns of everyday lives. This dissertation examines how changes to urban form and infrastructure influence residents' energy consumption and travel behaviour, and what these changes imply for urban decarbonization and well-being. The first paper studies the microclimatic role of urban tree canopy in moderating ambient temperatures and the extent to which this translates into reduced residential cooling demand. It also assesses how cooling benefits depend on canopy configuration relative to buildings and on weather conditions, highlighting when and where urban greening yields the largest energy savings. Shifting to the transport sector, the second paper evaluates how urban design, particularly the provision and expansion of cycling infrastructure, affects commute mode choice and the transition from motorized travel to more sustainable alternatives. The analysis further examines heterogeneity across socio-economic groups to identify which populations benefit most from increased exposure to cycling infrastructure along their commuting environments. The third paper investigates whether promoting cycling through infrastructure expansion delivers safety gains or whether changes in road design risk increasing collisions. It assesses safety outcomes for cyclists and for all road users and compares effects across facility types with different levels of physical separation from motor-vehicle traffic to inform design choices. Together, the three papers provide causal, policy-relevant evidence on how built-environment interventions can advance climate and sustainability goals while addressing heat mitigation, travel behaviour, and traffic safety.
Keywords: Urban sustainability; Urban climate mitigation; Causal impact evaluation; Built environment for GHG reduction